Case Report: Ascending Aortic Pseudo-Aneurysm Following Ventricular Septal Defect Repair in a 4-Year-Old Girl - Li, Xinya; Zhou, Hong; Zhang, Rui; Zhao, Jing; Li, Tian; Zhang, Yu; Ge, Jianjun (Frontiers in Pediatrics, 2021)
Pseudo-aneurysm is a fatal disease and the main cause of death is massive haemorrghage secondary to the rupture of the aneurysm. This case report aims to evaluate the effects of pseudo-aneurysm excision procedure on the disease. A 4-year-old girl was readmitted on 20th day after VSD closure procedure with a high fever of 40ºC, aortic pseudo-aneurysm was suspected based on a spherical cystic echo (82 x 76mm) of the ascending aorta was detected by ultrasonic cardiogram, and the diagnosis was confirmed by an aortic CTA examination and intraoperative findings. Treatment included emergency pseudo-aneurysm excision procedure and antibiotic therapy. The aortic pseudo-aneurysm was surgically removed under deep hypothermia and circulatory arrest. Antibiotics were applied according to the bacterial culture results. The pseudo-aneurysm was excised successfully, and the patient achieved a good recovery. Our case suggests that the postoperative ascending aortic pseudo-aneurysm probably due to inappropriate purse - string suture and/or local or systematic infection, so extra precautions should be taken to avoid this life-threatening complication.